Impact of Leading by Example on Employees' Organizational and Job Psychological Ownership: A Moderated Mediation Study - Ye, ZhiXiao; Shang, Xianfa; Shafait, Zahid; Xu, Youli (Frontiers in Psychology, 2022)
This paper studies the influence of leading by example on organizational psychological ownership and job psychological ownership. This paper further introduces the mediating mechanism of organizational identification and the regulating mechanism of leader-member Exchange (LMX). This paper investigated 312 personnel from 8 property management enterprises from East, Northwest, Northeast and central China. This study adopts quantitative research method, using survey data of project managers, team leaders and managers of Property management projects in China. The data were collected by questionnaire survey. In terms of data analysis, AMOS 21.0 software was used to conduct structural equation modeling (SEM) using maximum likelihood method to test direct and indirect effects. SPSS 25.0 software was used to test the moderating effect by multilevel regression analysis with maximum variance method. Use these two methods to analyze the whole theoretical framework. The results established all assumed relationships. In this paper, leading by example, one of the important dimensions of empowering leadership is studied as a new leadership style, and the predictive effect of leading by example on organizational psychological ownership and job psychological ownership is verified. This finding further verifies the influence mechanism and boundary conditions of empowering leadership in different dimensions. It is found that organizational identification has different mediating effects on leading by example and organizational psychological ownership, job psychological ownership. The moderating effect of LMX also further indicates that under the influence of Confucian pan-family culture, the leader's exemplary behavior with higher authority has stronger influence on employees' organizational identification and organizational psychological ownership and job psychological ownership. Their relationship is deeply influenced by the culture of with China's unique organizational Circle Culture.